Biosynthesis And Characterization Of Novel Polyhydroxyalkanoate By Cupriavidus Necator PHB-4 Transformant Harboring PHA Synthase Gene Of Chromobacterium SP. USM2 - Ooi, Tin Fong (2011)
In this study, a transformant of C. necator PHB-4 harboring the PHA synthase gene of Chromobacterium sp. USM2 [C.necator PHB 4 (phaCcs)] was evaluated for its ability to synthesize novel short-chain and medium-chain-length (SCL-MCL) PHA containing 3H4MV. Dalam kajian ini, transforman Cupriavidus necator PHB-4 yang menampung gen sintase PHA daripada Chromobacterium sp. USM2 [C.necator PHB 4 (phaCcs)] dinilai potensinya untuk mensintesis PHA novel iaitu PHA rantaian-pendek dan rantaian-sederhana-panjang (SCL-MCL) yang mana ia mengandungi 3H4MV.